The Global War for Internet Governance - LAURA DENARDIS (Yale University Press, 2014)
internet governance conflicts are the new spaces where politi cal and economic power is unfolding in the twenty- fi rst century. Technologies of Internet governance increasingly mediate civil liberties such as freedom of expression and individual privacy. They are entangled with the preservation of national security and the arbitration of digital commerce and innovation. The diff use nature of Internet governance technologies is shifting historic control over these public interest areas from traditional nation- state bureaucracy to private ordering and new global institutions. Many of these governance functions are technically and institutionally complicated and therefore out of public view. Yet how confl icts over Internet governance are settled will determine some of the most important public interest issues of our time. The term â€œInternet governanceâ€ conjures up a host of seemingly unrelated global controversies such as the prolonged Internet outage in Egypt during po liti cal turmoil or Googleâ€™s decision not to acquiesce to U.S. government requests to completely remove an incendiary po liti cal video from YouTube. It invokes media narratives about the United Nations trying to â€œtake overâ€ the Internet, cybersecurity concerns such as denial of ser vice attacks, and the mercurial privacy policies of social media companies. These issues exist only at the surface of a technologically concealed and institutionally complex ecosystem of governance.